Building a Generation of Strong Character in Kuta Baro Village through Positive Parenting Strategies - Sari Rizki; Rudy Juli Saputra; Najmuddin Najmuddin; Khairunnisak Khairunnisak (Civiliza Publishing, 2025)
The family plays a central role in shaping children’s character through daily interaction, role modelling, communication, and discipline. However, limited parental knowledge of empathetic communication, emotional regulation, positive reinforcement, and nonviolent discipline may reduce the effectiveness of parenting practices. This lecturer-led community service program aimed to strengthen the knowledge and practical skills of parents and primary caregivers in Kuta Baro Village in implementing positive parenting strategies to support children’s character development. The program involved 30 participants and employed a participatory educational approach consisting of needs assessment, interactive presentations, group discussions, case-based learning, parent–child communication simulations, and reflection on existing parenting practices. The materials focused on child development, effective family communication, parental emotional regulation, positive behavioural reinforcement, role modelling, and consistent nonviolent discipline. Program evaluation was conducted using pre- and post-activity assessments, participant observation, and analysis of parenting action plans. The mean assessment score increased from 61.8 before the program to 85.6 after the program, indicating a 38.5% improvement in participants’ understanding. Participants also demonstrated greater ability to identify less adaptive parenting practices, formulate constructive responses to children’s behaviour, apply logical consequences, and develop parenting strategies appropriate to their family contexts. The program further increased participants’ awareness of the importance of consistency, emotional responsiveness, and parental example in fostering discipline, independence, responsibility, empathy, and social concern. These findings demonstrate that participatory positive parenting education can serve as an effective community empowerment strategy for strengthening parental capacity and supporting children’s character development in Kuta Baro Village. Continuous mentoring and a parent learning forum are recommended to sustain the program’s outcomes.